Managing human resources - Can, Arthur W. (College Division, 1992)
Based upon current research, this book is practical with company examples, and has a full-colour design. 600 references have been added to this edition - many with 1991 citations. Coverage includes: employee rights; corporate culture; pay-for-performance; legal issues; and safety issues regarding toxic chemicals, smoking, repetitive motion injuries and a drug-free workplace.